2020
DOI: 10.2174/1574884715666200116104754
|View full text |Cite
|
Sign up to set email alerts
|

Medication Non-adherence in Patients with Osteoporosis: Implications for Clinical Pharmacists and Osteoporosis Care Providers

Abstract: Background : Poor adherence to the prescribed therapy leads to low bone mineral density and enhance the development of osteoporosis complications and unnecessary hospitalization. Objective : To explore factors associated with medication non-adherence in patients with osteoporosis. Findings would help guide the development of future pharmaceutical care interventions aim at improving health outcomes for patients with osteoporosis. Method: The study was conducted at an outpatient osteoporosis clinic at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…44 In a recent Jordanian study among patients with osteoporosis, it has been observed that the medication non-adherence was affected by the increased number of prescribed medications. 46 Therefore, a simplified regimen possibly with STR or fixed-dose combination might provide a reasonable clinical solution to improve adherence. Moreover, a metaanalysis by Igaly et al has indicated that once-weekly dosing of treatment for osteoporosis was associated with better adherence levels and higher odds of being adherent as compared to the once-daily dosing.…”
Section: Combination Of More Than One Simplification Strategymentioning
confidence: 99%
“…44 In a recent Jordanian study among patients with osteoporosis, it has been observed that the medication non-adherence was affected by the increased number of prescribed medications. 46 Therefore, a simplified regimen possibly with STR or fixed-dose combination might provide a reasonable clinical solution to improve adherence. Moreover, a metaanalysis by Igaly et al has indicated that once-weekly dosing of treatment for osteoporosis was associated with better adherence levels and higher odds of being adherent as compared to the once-daily dosing.…”
Section: Combination Of More Than One Simplification Strategymentioning
confidence: 99%
“…25,26 Similar findings were also reported in Jordanian patients with osteoporosis who reported 72.3% medication non-adherence rate. 27 Better medication adherence rate to anti-diabetics (72.4%), antihypertensive (50.7%) and lipid-lowering medications (44.3%) were reported in an elderly population in Spain. 28 A meta-analysis study reported that statins represent the most effective treatment to control lipid levels and to decrease the risk TA B L E 1 Characteristics of the study participants (n = 228) of stroke and coronary artery disease in all age groups.…”
Section: Discussionmentioning
confidence: 90%
“…Increased treatment complexity by the administration of several doses or prescribing multiple medications have been associated with low adherence levels 32 . A study conducted at an outpatient osteoporosis clinic at the Royal Medical Services Hospital in Jordan reported that patients were less likely to adhere to the prescribed medications with each unit increase in the number of prescribed medications 27 . Other studies revealed that the increased number of prescribed medications and the frequency of administration were associated with medication non‐adherence in patients with type 2 diabetes 33‐35 …”
Section: Discussionmentioning
confidence: 99%
“…Available data revealed that adherence to medications among patients suffering from chronic diseases averages 50% in the developed countries [3]. In the MENA region, including Jordan, these rates have been showed to be even lower [4][5][6][7][8][9][10]. In a study conducted among Jordanians receiving long-term treatment for different conditions, most of the participants showed to have poor adherence to their treatments [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted among Jordanians receiving long-term treatment for different conditions, most of the participants showed to have poor adherence to their treatments [4]. When looking to patients taking chronic medications for specific chronic diseases such as COPD, asthma or osteoporosis, the results were comparable, also demonstrating low rates of adherence [5][6][7]. In the MENA region, few studies reporting results from different middle eastern countries confirmed the presence of nonadherence as a problem among patients with chronic diseases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%